DAMPAK IMPLEMENTASI IFRS TERHADAP PENDIDIKAN AKUNTANSI DI INDONESIA - Nining Ika Wahyuni (Universitas Jember, 2011)
This study aims to explore fundamental issues related to the full adoption IFRS in Indonesia, include how accounting education anticipate the application of IFRS in 2012, the readinessof Indonesia's accountants to face the implementation of IFRS and accounting services liberalization and readiness of PPA to create accountants who have the competence and able to compete in the global marketplace. The research method used in this paper is descriptive research method by using data from various literature sources such as books, information from mass media as well as from the Internet. The results of this study indicate that implementation of IFRS will take many changes in mindset, paradigm and patterns of accounting’s teaching. Curriculum improvements must be done to create an accountant ready to compete in global market. Keyword: accounting education, IFRS